Efecto de la fertilización química en el rendimiento del cultivo de cacao (theobroma cacao l.) en la zona de baldramina alta cantón Quevedo - Noboa Gurumendi, Eduardo (2015)
Aiming to evaluate the effect of chemical fertilizers on crop yield cocoa (Theobroma cacao L.) in the area Baldramina high Quevedo canton. Whose geographical location is at an altitude of 70 meters. Its geographical coordinates are 65 ° 19 'west longitude and 6 ° 17' south latitude. field research was carried using a completely randomized design with 4 treatments and 4 repetitions Once the ANOVA statistical high significance for repetitions and treatments, the treatment had the highest average value was determined in terms of number of bearings was floral treatment T3: 20 - 10 to 30 NPK averaging bearings 14,21 and this average value as shown by statistically processing the value was 13.67 (T2: 20 - 20 to 20) and upper to 11.41 (T1: 10 - 30 to 10), the treatment had the highest average value of number of ears per plot was the T3: 20 - 10 to 30 with an average of 1373.71 ears, a value that is statistically equal to the average of the other treatments and superior to the control values of 1253.30 (T2: 20 - 20-20), 1230.50 (T1: 10 - 30-10) and 808.69 (Witness), in the cobs weight of the NPK T3 treatment showed 800 g ha-1, with an average of 1091.59 g, this value being statistically equal to the average treatment T2 NP 600 g which earned an average of 1017.51 g, the average value highest ear length was the T3: 20 - 10 to 30 with an average of 22.39 cm, this value being statistically equal to the average of treatments T2: 20 - 20 to 20 and T1: 10 - 30 - 10 with averages of 21.97 and 21.80 cm, the highest average diameter of ears showed the treatment T3: 20 - 10 to 30 with 13,49 cm, this value being statistically equal to the average of the other treatments and the Witness with averages of 13.13 cm (T2: 20 - 20-20), 12,31cm (T1: 10 - 30-10) and 8.94 cm for the control, analysis T3 treatment: 10 - 20 to 30, he presented the highest values of production costs $ 1 570.00, total revenues $ 3 961.22 estimated net income of $ 2 391.22 and benefit cost 1.52. On the other hand the lowest cost reported by the Witness with a value of $ 947.00.